Ethical issues associated with medical tourism in Africa - John J. O. Mogaka; Lucia Mupara; Joyce M Tsoka-Gwegweni (Taylor & Francis Group, 2017)
Global disparities in medical technologies, laws, economic inequities, and social-cultural differences drive medical tourism (MT), the practice of travelling to consume healthcare that is either too delayed, unavailable, unaffordable or legally proscribed at home. Africa is simultaneously a source and destination for MT. MT however, presents a new and challenging health ethics frontier, being largely unregulated and characterized by policy contradictions, minority discrimination and conflict of interest among role-players. This article assesses the level of knowledge of MT and its associated ethical issues in Africa; it also identifies critical research gaps on the subject in the region. Exploratory design guided by Arksey and O'Malley's (2005) framework was used. Key search terms and prior determined exclusion/inclusion criteria were used to identify relevant literature sources. Fifty-seven articles met the inclusion criteria. Distributive justice, healthcare resource allocation, experimental treatments and organ transplant were the most common ethical issues of medical tourism in Africa. The dearth of robust engagement of MT and healthcare ethics, as identified through this review, calls for more rigorous research on this subject. Although the bulk of the medical tourism industry is driven by global legal disparities based on ethical considerations, little attention has been given to this subject.